REDUCTION IN REVENUE VOLATILITY IN MAIZE PRODUCTION APPLYING THE INDIRECT-INDEX INSURANCE - Todor Marković; Sanjin Ivanović; Saša Todorović (Ekonomika Poljoprivrede (1979), 2013)
This paper is aimed at providing the basic theoretical postulates of indirect-index insurance and by its application at quantifying the effect of the reduction in risk using a stochastic simulation. The paper uses data on maize yield gathered from family farm in the central part of Srem, and weather data were acquired from the nearest referential meteorological station. For the purpose of achieving a stated aim, two situations were analysed: maize production value by using the indirect-index insurance and by using no indirect-index insurance. In the case of applying this type of insurance, a farmer can decrease the risk by 8,816 RSD/ha (r=1.0), 4,116 RSD/ha if the correlation coefficient is 0.8, that is 2,598 RSD/ha (r=0.6). Therefore, it is possible to conclude that there is a significant effect of the reduction in risk by applying indirect-index insurance.